SOSIALISASI GREEN PRODUCT DI INDUSTRI KECIL MENENGAH (IKM) TAHU DAN TEMPE DESA LAMBUSA KABUPATEN KONAWE SELATAN - Rizki, Selvi Diliyanti; Thahir, An Najjar Madjiani; Hakim, Al Asy Ari Adnan; Shaleha, Waode Maratun; Maksar, Muhammad Sofian; Badia, Bahdin Ahad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
The purpose of this socialization was to increase the understanding and awareness of tofu and tempeh small and medium industries (SMIs) in Lambusa Village about the concept and benefits of green products in producing environmentally friendly products. The methods used were lectures, discussions, and simulations of green product implementation in the tofu and tempeh production process. The results of the socialization activity showed an increase in participants' understanding of the concept and benefits of green products. Participants were also enthusiastic about implementing it despite constraints on limited capital and knowledge of environmentally friendly technologies. The service team provided affordable alternative solutions, such as waste utilization and energy savings. This socialization activity succeeded in raising awareness among tofu and tempeh SMIs about the importance of producing environmentally friendly products to increase competitiveness and business sustainability